Evaluation of Diagnostic Accuracy of Typhidot Test Against Blood Culture in Diagnosis of Enteric Fever - Mohsan Sohail, Anam Nazeer, Sarah Azhar, Ghazal Irfan, Saba Abrar, Muhammad Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the accuracy of Typhidot test against blood culture to diagnose Enteric Fever. Design of Study: Cross-sectional study Place and Period of study: Arif Memorial Teaching Hospital from August 2019 to Jan 2020. Material and Method: A total number of 89 cases who were fulfilled the inclusion criteria with signs & symptoms of Enteric fever. Results: There were 40 (44.9%) males and 49 (55.1%) females. 60 (67.4%) patients had positive Typhidot test while 69 (77.5%) showed positive blood culture. The typhidot showed sensitivity of 68.1%, specificity of 35%, PPV (Postive Predictive value) of 78.3%, NPV (Negtive Predictive value) of 24.1% and diagnostic accuracy of 60.7% against culture (gold standard). Conclusion: The study concludes that sensitivity & specificity of Typhidot test is less as compare to blood culture in diagnosing Enteric fever. Keyword: Typhoid Test, Enteric fever, Blood culture, Typhidot Test, Diagnostic accuracy